Sustainability Reporting Practices Of Listed Firms On The Ghana Stock Exchange And Its Determinants - Peter, D. (University of Ghana, 2020)
The purpose of the study is to analyse the sustainability reporting practices of firms on the Ghana Stock Exchange as well as the factors that influence such practices. Using the Triple-Bottom-Line (TBL) approach, the study conducted a quantitative content analysis of various reports of firms that contains sustainability information to determine the trends and focus of reporting of the sampled firms. The study retrieved 129 firm-years reports from firms listed on the Ghana Stock Exchange (GSE) over 5 years (2015 to 2019). Regression analysis was conducted to examine the determinants of the sustainability reporting practices of these firms and the effect of these practices on financial performance. The study explains the relationships on the premise of the stakeholder-legitimacy-signalling framework. The findings of the study reveal that listed firms in Ghana report more on economic sustainability than environmental and social dimensions as espoused by the Global Reporting Initiative (GRI) standard and the level of overall sustainability reporting is low. Even though the extent of reporting by environmentally and socially exposed firms is higher than that of less exposed firms, surprisingly some environmentally-sensitive firms produce no information on their environmental and social impacts. Again, the study finds governance mechanisms, firm size, liquidity, and industry affiliation to be the most predictors of sustainability reporting practices. Lastly, Financial performance was found to have a significant negative relationship with sustainability reporting practices when the market- base metric (Tobin’s Q) is used and insignificant when ROA is used. The study makes recommendations for policy and practice that policies should be designed to make the practice mandatory. Firms are also encouraged to subscribe to the GRI standard to ensure full advantage of sustainability.
MPhil. Accounting
Keywords: Sustainability; Ghana; Stakeholder; Financial